All Days 2003
DOI: 10.4043/15242-ms
|View full text |Cite
|
Sign up to set email alerts
|

Model Test Experience on Vortex Induced Vibrations of Truss Spars

Abstract: In order to evaluate the Vortex Induced Vibration (VIV) response of truss Spars and to optimize their strake configuration several model test programs have been carried out at MARIN. The results show that it is possible to optimize the strake design of Spars to obtain minimum VIV-response. The results of the model tests also suggest that modeling details, such as appendages, can have an influence on the Vortex Induced Vibrations. In order to reliably predict the full-scale VIV-behavior of the prototype Spar th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 3 publications
0
10
0
1
Order By: Relevance
“…Some studies on VIM of spars with consideration of appurtenances have been carried out by others [2], [3], [4], [5]. While helical strakes alone are effective in suppressing VIM, albeit this behavior is heading dependent, the presence of other appurtenances namely anodes, pipes and chains together with the strakes may result in significantly higher VIM in spars [3].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on VIM of spars with consideration of appurtenances have been carried out by others [2], [3], [4], [5]. While helical strakes alone are effective in suppressing VIM, albeit this behavior is heading dependent, the presence of other appurtenances namely anodes, pipes and chains together with the strakes may result in significantly higher VIM in spars [3].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the small-scale experiments on a truss spar platform performed by van Dijk et al [1] already showed that, despite the strong susceptibility to geometric aspects of the hull, the VIM phenomenon clearly presents both the self-excitation and the selfcontrolled characteristics, in general terms, similar to the VIV on risers. Moreover, despite focused on mitigating the effects of VIM on such a type of platform by adding strakes, those authors also showed that, without suppressors, the maximum response amplitude occurs in a range of reduced velocities between 5 and 9, making explicit mention to eight-shaped trajectories, in a quite evident coupling between the in-line and transverse motions.…”
Section: Introductionmentioning
confidence: 92%
“…It is important for keeping the similarity between prototype and model. Thus, the Froude scaling approach recommended by van Dijk et al [23] was used. It is essential to note that the Reynolds number (Re = UD/ν, where U is the current velocity, D is the projected width of the column and ν is the kinematic viscosity of the fresh water) for the prototype DDS is in the order of 10 7 while the Reynolds number at model scale is significantly lower.…”
Section: Model Set-upmentioning
confidence: 99%